2021
DOI: 10.1002/pssr.202100196
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Microwave Synthesis of WO3 Nanostructured Films for Solar Photocatalysis

Abstract: Tungsten oxide (WO3) nanostructured films are synthesized under microwave radiation with synthesis times of 5 and 10 min, at 150 or 180 °C. This ultrafast synthesis route results in uniform and well‐crystallized WO3 nanostructured films fully covering the substrates. A plate‐like hierarchical structure is observed at 150 °C, and closely packed rectangular nanorods are formed at 180 °C. For both temperatures, the nanostructures self‐organize into larger flower‐like structures. The increase of the synthesis time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 100 publications
(181 reference statements)
1
7
0
Order By: Relevance
“…The other two peaks observed at 324 cm −1 and 270 cm −1 correspond to the W–O–W bending mode of vibration. 14,22,42 No impurity phases were observed. When coming to the WO 3− x sample, with sulfur treatment, a broadening has been observed in the characteristics of the Raman bands.…”
Section: Resultsmentioning
confidence: 96%
“…The other two peaks observed at 324 cm −1 and 270 cm −1 correspond to the W–O–W bending mode of vibration. 14,22,42 No impurity phases were observed. When coming to the WO 3− x sample, with sulfur treatment, a broadening has been observed in the characteristics of the Raman bands.…”
Section: Resultsmentioning
confidence: 96%
“…Despite the considerable efficiency loss after three cycles (of around 21%), a much smaller efficiency loss was observed during the next cycles. This loss could be attributed to the high adsorption phenomenon of RhB, where RhB molecules remain adsorbed on the photocatalyst surface, hindering the available pore sites of the substrate with the nanostructures for reaction [ 123 , 124 ]. The reusability tests of the pristine substrate confirmed that a significant contribution to this loss of degradation efficiency comes from the substrate, with the adsorption of RhB molecules through the cycling tests (see Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…After performing three consecutive cycles, a decolorization efficiency loss of around 22% was obtained. Since neither heat/UV treatments nor rinsing were applied to the substrate between cycles, a high percentage of RhB molecules could have remained from the previous cycle adsorbed on the photocatalyst surface, hindering the available pore sites on the TiO 2 functionalized cork substrate for reaction [13,125], thus decreasing its overall cycling efficiency. This effect has been previously reported in different studies [13,23,125,126].…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Different materials and, more frequently, metal oxide semiconductors have been studied for the development of efficient photocatalysts, including WO 3 [13], Fe 2 O 3 [14], ZrO 2 [15], SrTiO 3 [16], ZnO [17,18] and TiO 2 [19][20][21][22][23][24]. Among these semiconductors, TiO 2 has been extensively studied for photocatalysis since it is the most promising material for industrial use [25], due to its physical and chemical stabilities, low-cost, non-toxicity and strong oxidation potential to decompose organic pollutants [20,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%